2012
DOI: 10.1016/j.jbiomech.2012.05.048
|View full text |Cite
|
Sign up to set email alerts
|

Identification of scapular kinematics using surface mapping: A validation study

Abstract: The immediate goal of this study was to develop and validate a noninvasive, computational surface mapping approach for measuring scapular kinematics by using available motion capture technology in an innovative manner. The long-term goal is to facilitate clinical determination of the role of the scapula in children with brachial plexus birth palsy (BPBP). The population for this study consisted of fourteen healthy adults with prominent scapulae. Subject-specific scapular templates were created using the coordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…Five studies had a quality score between 70% and 80% (Meskers et al, 2007;Bourne et al, 2009;Lempereur et al, 2010;Senk and Cheze, 2010;Chu et al, 2012) and 8 between 60% and 70% (Karduna et al, 2001;Lovern et al, 2009;Brochard et al, 2011b;Prinold et al, 2011;Shaheen et al, 2011;Mattson et al, 2012).…”
Section: Quality Of Reviewed Articlesmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies had a quality score between 70% and 80% (Meskers et al, 2007;Bourne et al, 2009;Lempereur et al, 2010;Senk and Cheze, 2010;Chu et al, 2012) and 8 between 60% and 70% (Karduna et al, 2001;Lovern et al, 2009;Brochard et al, 2011b;Prinold et al, 2011;Shaheen et al, 2011;Mattson et al, 2012).…”
Section: Quality Of Reviewed Articlesmentioning
confidence: 99%
“…Three studies put the markers on the anatomical landmarks of the scapula recommended by the ISB (AA, AI and TS) (Lovern et al, 2009;Lempereur et al, 2010;Brochard et al, 2011b). Bourne et al (2009) used 6 surface marker configurations on the scapula whereas Mattson et al (2012) fixed 300 markers on the scapula. Lempereur et al (2010) showed that the use of markers on the scapula produced an error (in comparison with palpation) of up to 15° with increasing humeral elevation Lovern et al (2009) found an under-estimation of 50° of upward rotation at full arm elevation.…”
Section: Marker Placements Other Than On the Acromionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the upper extremity, the scapula is particularly affected. To solve this issue, several techniques were proposed, such as the scapula locator device [4], the acromion marker cluster [5,6] or the use of a large number of markers to track skin deformation and infer scapular motion [7].…”
Section: Introductionmentioning
confidence: 99%